2020
DOI: 10.1021/acs.langmuir.0c02369
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Control of Ferrofluid Droplet Adhesion in Shear Flow and on Inclined Surfaces

Abstract: The manipulation of ferrofluidic droplets by magnetic fields is a popular technique for controlling fluid transport in open microfluidic systems. We examine the effect of gravity and shear flow external forces on the adhesion properties of sessile ferrofluidic droplets in the presence of a uniform magnetic field. The magnetic field was found to enhance the critical Bond number at which sliding begins on a tilting substrate but suppress the critical Weber number at which sliding begins in a moderate Reynolds nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 50 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…It must be noted that the saturated value of ξ max is increasing with the increase of polymer concentrations. One of the potential reason for the initial linear increase of ξ max with Bo m is due to the linear magnetization of the ferrofluid droplet , in the low field regime. In a previous report, it has been shown that PEG chains may entangle Fe 3 O 4 nanoparticles to form a particle–polymer chain mesh.…”
Section: Resultsmentioning
confidence: 99%
“…It must be noted that the saturated value of ξ max is increasing with the increase of polymer concentrations. One of the potential reason for the initial linear increase of ξ max with Bo m is due to the linear magnetization of the ferrofluid droplet , in the low field regime. In a previous report, it has been shown that PEG chains may entangle Fe 3 O 4 nanoparticles to form a particle–polymer chain mesh.…”
Section: Resultsmentioning
confidence: 99%
“…Concomitant with the progress in microfluidic technologies, droplet microfluidics realizes the flow control of microdroplets and builds a new platform for biological and medical research. Until now, a variety of droplet control methods such as electrowetting [13,14], optical tweezers [15,16], acoustic manipulation [17], and magnetic manipulation [18][19][20] have been developed to transport, sort, split, merge and mix droplets.…”
Section: Introductionmentioning
confidence: 99%
“…The critical flow velocity under different driving frequencies and an external magnetic field can be determined according to the growth rate and decay rate of interface fluctuation. Cui [16] studied the effect of gravity and shear flow on adhesion of magnetic fluid and found that the enhancement of a vertical magnetic field could improve the critical magnetic Bond number and reduce the critical Weber number, which makes the magnetic droplet more susceptible to shear flow. Bohlius [17] deduced the dispersion relationship of interfacial waves in magnetic films under a vertical magnetic field.…”
Section: Introductionmentioning
confidence: 99%